Spiritual resiliency in older women : models of strength for challenges through the life span - Ramsey, Janet L. (Sage Publications, 1999)
Spiritual Resiliency records the narratives of spiritually resilient German and American women, who represent a group rarely considered: strong, old women. They point to the need to incorporate spiritual coping in the counselling repertoire.